Pengaruh Faktor Eksternal dan Internal terhadap Nilai Aktiva Bersih Reksadana Syariah Saham Sebelum dan Selama Covid-19 (2018-2021) - Ratih Sulistia; Tjetjep Djuwarsa; Radia Purbayati (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this study was to determine the influence of external and internal factors, namely GDP, inflation, gold prices, operational performance, age of mutual funds, and size of mutualifunds on Net Asset Value (NAV) of sharia equity mutualifunds and knowing the differences in NAV of sharia equity mutual funds before and during Covid-19 from 2018 to 2021. Data were processed using panel data regression analysis techniques and the Wilcoxon Signed Ranks Test. The results of this research studyiare thatipartially GDP, inflation, gold prices, operational performance, and mutual fund age have no significant effect onithe NAV ofishariaiequity mutualifunds. Meanwhile, mutualifund size has a significant effect on the NAV of sharia equity mutual funds. Furthermore, the results of the different test showithat there is no difference inithe NAV ofisharia equityimutual funds in shares that occurred beforeiand duringiCovid-19. Keywords: Net Asset Value, External Factors, Internal Factors, Covid-19, Sharia Equity Mutual Funds.